Physiology of echinoderms. - Binyon, John (International series of monographs on pure and applied biology. Division, Zoology, 1972)
Physiology of Echinoderms is an 11-chapter book that begins by elucidating the feeding, digestion, and excretion of specific echinoderms. The critical role of amoebocytes in the excretion process involved in these organisms is also explained. This book also describes several aspects of importance to these organisms, including salinity tolerance, osmoregulation, ionic regulation, chemical composition, neural control of locomotion, biochemical affinities, toxins, and immunology. The organisms' physiology in sensory, water vascular system, respiratory system, spawning, neurosecretion, nerves, and.